Escuela Normal (Normal School) of Costa Rica: History and Legacy - Carvajal-Jiménez, Vivian (2016)
On the centennial of the Escuela Normal (Normal School) of Costa Rica, this paper discusses its role and its legacy in teacher training. It is structured in three parts. Firstly, it presents a brief historical background of the origin and profile of normal schools in various parts of the world. Secondly, it describes the development of the Escuela Normal (Normal School) in Costa Rica, refers to various personalities and significant elements that have set the course and prestige of the institution, and places the emphasis on its key role in the humanistic training of teachers, which helped to establish the foundations of Costa Rican educational development. Finally, it presents some remarks about the educational legacy of this noble institution that has remained to this day, particularly in tertiary education, in the teacher training career at the National University, the major historical heir of the Escuela Normal (Normal School).